1983
DOI: 10.1159/000198946
|View full text |Cite
|
Sign up to set email alerts
|

Protective Action of Omeprazole, a Benzimidazole Derivative, on Gastric Mucosal Damage by Aspirin and Ethanol in Rats

Abstract: This study was designed to compare the influence of omeprazole, a potent inhibitor of H+/K+-ATP-ase involved in the final step of H+ secretion and prostaglandin (PG) I2 on the formation of gastric mucosal lesions induced by absolute ethanol or acidified aspirin (ASA). Omeprazole given intragastrically in both inhibitory (20 or 200 μmol/kg) and nonin-hibitory doses (2 μmol/kg) prevented dose dependently ASA- and ethanol-induced gastric lesions. The protective effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 4 publications
4
28
0
Order By: Relevance
“…In addition, FRG-8813 also proved to be effective in preventing the lesion formation even when the rats were pretreated with omeprazole (30 mg/kg, s.c.) at the dose required to suppress 2-DG-stimulated acid secretion by about 90010. In contrast, the gastroprotective effect of oral omeprazole used as a reference drug was completely attenuated by the same treatment, and this result is consistent with the previous reports (18,19). Since omeprazole is readily degraded by acidic pH (20), the degraded compounds produced in the gastric juice of the lumen are considered to exert the gastroprotective effect by a local action from the luminal side.…”
Section: Studies Of the Gastroprotective Mechanisms Of Frg-8813supporting
confidence: 89%
“…In addition, FRG-8813 also proved to be effective in preventing the lesion formation even when the rats were pretreated with omeprazole (30 mg/kg, s.c.) at the dose required to suppress 2-DG-stimulated acid secretion by about 90010. In contrast, the gastroprotective effect of oral omeprazole used as a reference drug was completely attenuated by the same treatment, and this result is consistent with the previous reports (18,19). Since omeprazole is readily degraded by acidic pH (20), the degraded compounds produced in the gastric juice of the lumen are considered to exert the gastroprotective effect by a local action from the luminal side.…”
Section: Studies Of the Gastroprotective Mechanisms Of Frg-8813supporting
confidence: 89%
“…Omeprazole, a proton-pump inhibitor, prevents dam age caused by necrotizing agents such as absolute ethanol and 35010 NaCl in rat gastric mucosa (1,2). This effect is also found in other proton-pump inhibitors (3)(4)(5).…”
mentioning
confidence: 77%
“…The mechanism of the cytoprotection is, however, not known. This effect of proton-pump inhibitors is observed only when the drugs are given intragastrically (2)(3)(4). So, pro ton-pump inhibitors might need to come in contact with gastric contents, especially gastric acid, to induce cyto protection.…”
mentioning
confidence: 99%
“…Konturek et al (20) has reported that omeprazole has no effect on the biosynthesis of gastric mucosal PGI2. Moreover, omeprazole has been reported to have no effects on the biosynthesis of PG in human tissue culture (21) or in isolated gastric mucosal cells from guinea pigs (22).…”
Section: Discussionmentioning
confidence: 99%